The palatability of Neotropical poison frogs in predator‐prey systems: do alkaloids make the difference?. (24th November 2016) - Schulte, Lisa M.; Saporito, Ralph A.; Davison, Ian; Summers, Kyle
Abstract: Neotropical poison frogs sequester alkaloid‐based chemical defenses from their diet, which seem to repel invertebrate predators after contact. In this study, we tested the reaction of predatory ants toward skin secretions of captive‐bred poison frogs without alkaloids. Although the secretions had a smell and taste similar to those of wild‐caught frogs, the ants did not avoid them, but actually preferred them. We infer that amphibian secretions are attractive to invertebrate predators (probably due to palatable nutritive components), but that this attraction is overridden when unpalatable alkaloids are present.